Antibiofilm activity of carotenoid crocetin against Staphylococcal strains - Paramanya, Saurav; Lee, Jin-Hyung; Lee, Jintae (Frontiers in Cellular and Infection Microbiology, 2024)
Staphylococcus aureus and Staphylococcus epidermidis stand as notorious threats to human beings owing to the myriad of infections they cause. The bacteria readily form biofilms that help in withstanding the effects of antibiotics and the immune system. Intending to combat the biofilm formation and reduce the virulence of the pathogens, we investigated the effects of carotenoids, crocetin, and crocin, on four Staphylococcal strains. Crocetin was found to be the most effective as it diminished the biofilm formation of S. aureus ATCC 6538 significantly at 50 µg/mL without exhibiting bactericidal effect (MIC >800 µg/mL) and also inhibited the formation of biofilm by MSSA 25923 and S. epidermidis at a concentration as low as 2 µg/mL, and that by methicillin-resistant S. aureus MW2 at 100 µg/mL. It displayed minimal to no antibiofilm efficacy on the Gram-negative strains Escherichia coli O157:H7 and Pseudomonas aeruginosa as well as a fungal strain of Candida albicans. It could also curb the formation of fibrils, which partly contributes to the biofilm formation in S. epidermidis. Additionally, the ADME analysis of crocetin proclaims how relatively non-toxic the chemical is. Also, crocetin displayed synergistic antibiofilm characteristics in combination with tobramycin. The presence of a polyene chain with carboxylic acid groups at its ends is hypothesized to contribute to the strong antibiofilm characteristics of crocetin. These findings suggest that using apocarotenoids, particularly crocetin might help curb the biofilm formation by S. aureus and S. epidermidis.